Comorbidities in the first 2 years after arthroscopic hip surgery: substantial increases in mental health disorders, chronic pain, substance abuse and cardiometabolic conditions. Issue 9 (27th September 2018) - Rhon, Daniel I; Greenlee, Tina A; Marchant, Bryant G; Sissel, Charles Dennis; Cook, Chad E
Abstract : Objectives: We aimed to identify the rate of seven comorbidities (mental health disorders, chronic pain, substance abuse disorders, cardiovascular disorders, metabolic syndrome, systemic arthropathy and sleep disorders) that occurred within 2 years after hip arthroscopy. Methods: Data from individuals (ages 18–50 years) undergoing arthroscopic hip surgery between 2004 and 2013 were collected from the Military Health System (MHS) Data Repository (MDR). The MDR captures all healthcare encounters in all settings and locations for individuals within the MHS. Person-level data over 36 months were pulled and aggregated. Seven comorbidities related to poor outcomes from musculoskeletal disorders (mental health disorders, chronic pain, substance abuse disorders, cardiovascular disorders, metabolic syndrome, systemic arthropathy and sleep disorders) were examined 12 months prior and 24 months after surgery. Changes in frequencies were calculated as were differences in proportions between presurgery and postsurgery. Results: 1870 subjects were identified (mean age 32.24 years; 55.5% men) and analysed. There were statistically significant increases (p<0.001) proportionally for all comorbidities after surgery. Relative to baseline, cases of mental health disorders rose 84%, chronic pain diagnoses increased 166%, substance abuse disorders rose 57%, cardiovascular disorders rose by 71%, metabolic syndrome cases rose 85.9%, systemic arthropathy rose 132% and sleep disorders rose 111%. Conclusions: Major (potentially 'hidden') clinical comorbidities increased substantially after elective arthroscopic hip surgery when compared with preoperative status. These comorbidities appear to have been overlooked in major studies evaluating the benefits and risks of arthroscopic hip surgery. Level of evidence: Prognostic, level III.